Development Results Agriculture With Make Product Processing Corn Ice Products to Increase Sale Value in Sumber Agung Village - Yusrudin, Yusrudin; Huda, Samsul (OJS Universitas Muhammadiyah Gresik, 2024)
Sumber Agung Village is located in the Mantup District, Lamongan Regency. The location of Sumber Agung Village is in Mantup Lamongan District, west of Sumberkerep Village, which borders Gresik and Lamongan. Sumber Agung Village consists of 3 hamlets, including: Hamlet Waru Lor, Hamlet Gempol Waru, And Hamlet Banjar Concubine. Village Source Agung has local potential from one of their agricultural products, namely corn. Corn is a food commodity strategic after paddy and become food source Alternatives that contain lots of nutrients. However, the people of Sumber Agung Village still do not have deep knowledge process as well as utilise results agriculture corn Activity training making Corn Ice products provided by Regular KKN Students at Muhammadiyah University Gresik are aimed at For public Village Source great To use can increase as well as optimizing the development of village potential with knowledge related to the creative economy of processing corn commodity agricultural products. This training was attended by 30 residents of Sumber Agung Village. This training is expected can increase Skills public in process results agriculture they are mainly corn and can create business opportunities, as well as increase people's income.